Efektivitas Jenis-Jenis Disinfektan Terhadap Virus Corona Unggas Secara In Ovo - Suwarno, Suwarno; Misaco Yuniarti, Wiwik; Anam Al-Arif, Mohammad; Rahmahani, Jola; Supriyadi, Supriyadi (LOSARI DIGITAL, 2024)
Efforts to maintain personal hygiene, health and environmental cleanliness, and prevent the spread of Covid-19 are by using disinfectants, either in the form of hand sanitizers or environmental disinfection. The lecture was conducted by inviting representatives of the Mosque/Mushlla Takmir throughout Surabaya City as many as 200 people. The lecture activity was centered at the Faculty of Veterinary Medicine, Airlangga University. Testing was carried out using TIB (embryo-bearing duck eggs) as a medium for the growth of coronavirus. All types of disinfectants used in this community service activity are very effective in neutralizing coronavirus. This is indicated by the absence of coronavirus growth in TAB, all showing negative results. This means that the coronavirus that has been disinfected using several disinfectants has died, so it cannot be grown in TAB. In the control group, coronavirus in chickens can cause defects in embryos, in the form of embryo dwarfism and defects in the toes. While in the treatment group given disinfectant, the coronavirus did not grow and did not cause changes in the embryo.